Evaluation the Effect of Bio-Fertilization on Some Wheat (Triticum Aestivum) Growth Parameters under Drought Conditions - Saad, Dina A.; Al-Shahwany, Ayyad W.; Aboud, Hadi M. (Iraqi Journal of Science, 2019)
Field experiment was conducted during 2018- 2019 in loam soil at the research field of the Department of Biology, College of Science, Baghdad University, Baghdad, Iraq, to study the effect of bio-fertilizers and two levels of chemical fertilization ( 50% and 100%) in some agronomic traits of wheat Triticum aestivum L. cultivar IPA 99 by the genus Azotobacter chroococum and AMF Glomus mosseae singly or in combination under drought condition. The experimental design was a Completely Randomized Block Design (CRBD)with three replications. The results revealed that the application of bio-fertilizers reduced the negative impacts of water deficit. However, (Azoto+AMF) were significantly increased the means of plant height, flag leaf area, flag leaf chlorophyll content and the fresh weight of total vegetative ( 86.81 cm, 65.45 cm2, 49.55 SPAD, 37.93 g) respectively compared to the control treatment at 20% water deficit and 50% fertilization. Besides, there was no antagonism between A. chroococcum and Glomus mosseae, which can recommend to use them as bio-fertilizer.